THE USE OF SUSTAINED SILENT READING TO IMPROVE STUDENT’S READING COMPREHENSION AT TENTH GRADE OF SMK PEMUDA TARUNA - Mohammad Fatoni; Khoirul Wafa; Yusrotun Nisa’ (Jurnal Ilmiah Hospitality, 2020)
The ability to understand English texts is very important especially for students. There were several problems that were faced by tenth grade students of SMK Pemuda Taruna about their reading comprehension. To improve student’s reading comprehension of tenth grade students of SMK Pemuda Taruna, the researcher used Sustained Silent Reading as a learning method. The researcher used Classroom Action Research to conduct this research and divided them into two cycles. The collected data in this research were analyzed by using observation sheet, test and field notes. The result of the data indicated that there were improvement in the students’ score of post-test cycle I and post-test cycle II. The average score of the pre-test was 53,6 (54), in the post-test cycle I increased 59,0 (59) and in the post-test cycle II the average score of students also increased 70,2 (70). From that result it can be concluded that, the use of SSR (Sustained Silent Reading) Method effective to improve students’ reading comprehension on narrative text especially legend text at tenth grade of SMK Pemuda Taruna.